Naphthoquinones from the leaves of Rhinacanthus nasutus having acetylcholinesterase inhibitory and cytotoxic activities - Sirada Boonyaketgoson (2018)
© 2017 Elsevier B.V. Four new naphthoquinones (1–4), named rhinacanthins S (1), T (2), U (3) and V (4), together with 13 known naphthoquinones were isolated from the leaf extract of Rhinacanthus nasutus. The structures of isolated compounds were elucidated by spectroscopic methods, especially 1D and 2D NMR spectroscopy and mass spectrometry. Rhinacanthin S (1) exhibited acetylcholinesterase inhibition activity with a % inhibition value of 48.04 ± 3.25. The known rhinacanthin A (5) showed cytotoxicity against a MCF-7 cell line with an IC50value of 8.79 μM, while rhinacanthin N (15) was active against the NCI-H187 cell line with an IC50= 2.24 μM and Vero cells (IC50= 3.00 μM)